NEW SOURCES OF FINANCE FOR THE FILM PRODUCTION - P. Ogurchikov; N. Skobeev (Вестник университета)
The refund mechanism for foreign producers on the example of the Hungarian system of incentives for foreign filmmakers is analyzed. The experience of granting tax incentives for film production of the EU countries is described. The problems limiting development of similar practice in Russia are identified.